Development and characterisation of a pressurized PEM bi‐stack electrolyser. (8th April 2012) - Millet, P.; Grigoriev, S. A.; Porembskiy, V. I.
SUMMARY The purpose of this communication is to report on the design and performances of a 3.0 Nm3 H2/hour bi‐stack PEM water electrolyser operating in the 1 – 150 bars pressure range. Data related to the electrochemical efficiency, faradic efficiency and gas purity as a function of operating temperature and pressure are presented and discussed, as well as performance stability on the long term. An efficiency of ca. 85 % (based on the higher heating value of hydrogen) has been measured at 500 mA.cm‐2 and 88 °C. High pressure tests have been successfully performed at 130 bars. At such elevated pressure, gas‐cross permeation effects substantially reduce the faradaic efficiency of the electrolyser. As a result, the energy consumption required to produce hydrogen increases, and the hydrogen concentration in oxygen on the anodic side reaches hazardous values. Some strategies used to manage such critical issues are discussed. Copyright © 2012 John Wiley & Sons, Ltd.